Pemahaman Pengaruh Peran Orang Tua Dan Ibadah Keluarga Terhadap Pertumbuhan Kerohanian Pemuda Gereja Masehi Advent Hari Ke-Tujuh Konferens Jawa Barat Cluster 2 - Simbolon, Bennyamin; Hutagalung, Stimson (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the church youth are often referred to as "the pillars of the future church", thus youth are an important part of the church, to carry out the great commission through the church. Thus, young people are needed who have good morals and spirituality. This research aims to examine the influence of parents and family worship on the spiritual growth of youth at the West Java Conference Seventh-day Adventist Church (WJC SDAC) Cluster. This research was created to prove the truth of the hypothesis that it is thought that the role of parents and family worship have a significant influence. significant impact on the spiritual growth of WJC SDAC Cluster 2 youth. This type of research is quantitative, using a survey with a descriptive analysis approach, involving 114 respondents representing parents in each WJC SDAC Cluster 2. This research instrument uses a questionnaire. The results of this research show the great significance of the role of parents and family worship in the spiritual growth of youth in WJC SDAC Cluster 2. The study shows that a significant number of parents agree that parental guidance has an effect on their children's moral and spiritual growth. and regular loyalty to family.